SLAUGHTER PARAMETERS AND CLASSIFICATION OF LAMB’S CARCASES OF SJENICA IMPROVED DOMESTIC TUFT SHEEP IN ACCORDANCE WITH EUROPEAN UNION REGULATION (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
The paper examines the slaughter values of lamb carcasses of Sjenica improved domestic tuft sheep at the age of three months. In addition, the classification according to the conformation and the degree of fat cover of the carcass was performed in accordance with the regulations of the European Union. The results of the research showed that the established differences in slaughter parameters of carcasses of male and female lambs were not statistically significant (p> 0.05). The conformation of the carcasses of both examined groups was assessed with 2.1 (p> 0.05). The degree of carcass coverage in male lambs was 2.4, while in females it was 2.3 (p> 0.05).